A CASE SERIES OF LISTERIA MONOCYTOGENES INFECTION IN INFLAMMATORY BOWEL DISEASE PATIENTS TREATED WITH ANTI-TNFα THERAPY. (8th June 2013) - Gray, J A; Allen, P B; Diong, K; Kane, M; Varghese, A
Abstract : Introduction: Anti-TNFα therapy has had a huge impact on the treatment of inflammatory bowel disease. The inhibition of TNFα not only reduces inflammation but also increases the risk of opportunistic infections. Intracellular organisms such as Myobacterium tuberculosis and Listeria monocytogenes are particularly high risk. Much has been written on TB with infliximab therapy whereas Listeria has not received similar attention. Case Series We report 2 cases of Listeria bacteraemia observed with infliximab for IBD. Case 1: A 65 year old male with known Crohns colitis presents with worsening diarrhoea & discharge. EUA and MRI confirm intersphincteric horsehoe fistula with moderate distal colitis. After failing steroid therapy he was commenced on infliximab. Ten days after his first dose he began to spike temperatures. Blood cultures confirmed Listeria monocytogenes bacteraemia. Case 2: A 50 year old male with known ulcerative colitis maintained on 5-ASA therapy presents with a severe exacerbation. He was commenced on infliximab after failing steroid therapy. After initially responding well to treatment he re-presented with flu-like symptoms and temperatures. Blood cultures confirmed Listeria monocytogenes. Both cases responded well to intra-venous amoxicillin. Of significance both patients presented within the loading dose period and were also receiving azathioprine and corticosteroids. Currently only 17 cases of invasive Listeriosis secondary to anti-TNFα therapy have been observed in IBD patients. Conclusion: We conclude that patients requiring anti-TNF? therapy should be informed of the risk of food borne infections and advised to avoid high risk foods. These cases highlight the need for strict guidelines and prescribing physicians to be aware of such complications.